KORELASI KLINIKO-SITOPATOLOGI PADA APUSAN SERVIKS DENGAN GAMBARAN EPITHELIAL CELL ABNORMALITIES (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2018)
Cervical cancer is one of the most cancer experienced by women in the world. Periodic examination of cervical smears can reduce cancer mortality by 40%, especially in women aged over 50 years. In populations with extensive screening coverage, the incidence of cervical cancer drops to 70-90%, while in non-screening populations, the incidence of cervical cancer continues to be in preliminary conditions as when screening has not yet been implemented in developed countries. This study aims to assess the correlation between clinical features and cytopathology of cervical smears that have epithelial cell abnormalities in accordance with the Bethesda classification. This research is an analytical research with cross sectional technique to know the correlation of clinical characteristic with cytopathology picture on cervical smear. The study was conducted in May-October 2017 at Anatomical Pathology Laboratory of Medical and Health Sciences, and examination of cervical smear in pubic health centre of Tembesi. Cytopathologic variables were epithelial cell abnormality according to Bethesda criteria of NILM, ASCUS, LSIL, HSIL, squamous cell carcinoma and glandular cell abnormalities. There were 80 people who met the inclusion criteria. In this study, the most age group was found in 30-45 years as many as 48 or 60.0%, multiparity as much as 67 or 83.8%, the most widely used type of contraception is IUD as much as 33 or 41.3%. Of all the variables only significant correlation of clinical characteristic was found on contraceptive pill using pill / ASCUS (100%) and SIL (100%), and implant with HSIL (100%). Keywords : Clinico-cytopathology, Cervical, Epithelial Cell Abnormality